2018
DOI: 10.1186/s12913-018-3585-9
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the development of assisted reproductive technology in Liaoning province of China, from 2012 to 2016

Abstract: BackgroundThe development of assisted reproduction techniques (ART) has resulted in rapid advances in the treatment of infertility. However, a systematic assessment of ART and its processes and outcomes in China has never been carried out. The goal of this study was to assess the features of ART status from 2012 to 2016 in clinics and in vitro fertilization (IVF) laboratories in Liaoning, the largest IVF province in the northeast of China.MethodsData from Jan 1, 2012 to Dec 31, 2016 was retrieved from the assi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…While EBM looks these three cornerstone of evidence in a broad way, clinical decisions made on these evidence can be more individual and precise (Martins et al, 2018). Clinicians can adjust the dosages of hCG based on patients' remaining ovarian reserve and BMI, select specific fertilization techniques according to sperm features and clinical background, and monitor embryo development in vitro (Fang et al, 2018). In addition, gene profiles are a more precise guide to treatment.…”
Section: Clinical Decisionsmentioning
confidence: 99%
See 1 more Smart Citation
“…While EBM looks these three cornerstone of evidence in a broad way, clinical decisions made on these evidence can be more individual and precise (Martins et al, 2018). Clinicians can adjust the dosages of hCG based on patients' remaining ovarian reserve and BMI, select specific fertilization techniques according to sperm features and clinical background, and monitor embryo development in vitro (Fang et al, 2018). In addition, gene profiles are a more precise guide to treatment.…”
Section: Clinical Decisionsmentioning
confidence: 99%
“…The success rate has been elevated, but it is still approximately 40%, which is consistent with the data provided from other regions. In summary, efficiency is a problem that urgently needs to be solved, and reproductive medicine should be more precise (Fang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…According to information collected by Boivin et al (2007) approximately 15% of couples of reproductive age suffer infertility. In Northeast China, 18% male-only factors and 20% combined male and female infertility were found in assisted reproductive technology (ART) patients (Fang et al, 2018). Infertility patterns are conventionally divided into primary and secondary types; the former indicates a failure to become pregnant after 1 year, and the latter indicates an inability to become pregnant after 1 year after previously having fathered one or more biological children (Mohamed et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Infertility patterns are conventionally divided into primary and secondary types; the former indicates a failure to become pregnant after 1 year, and the latter indicates an inability to become pregnant after 1 year after previously having fathered one or more biological children (Mohamed et al, 2017). Previous studies have shown that the proportion of primary infertility decreased while the proportion of secondary infertility increased in China from 2012 to 2016 (Fang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The WHO reported that approximately 15% of couples worldwide and 7% of the male population have infertility (Krausz & Riera‐Escamilla, 2018; Sahin, Urkmez, Verit, Yuksel, & Verit, 2017). In Northeast China, 18% male‐only factors and 20% combined male and female infertility were found in assisted reproductive technology (ART) patients (Fang et al., 2018). A number of factors could induce male infertility, including genetics, environment and lifestyle (Hotaling & Carrell, 2014; Yao & Mills, 2016).…”
Section: Introductionmentioning
confidence: 99%